Stability augmentation of interconnected offshore wind and marine current farms - Shawon, M.; Al-Durra, A.; Muyeen, S.M. (2011)
This paper presents a co-operative control scheme for a small scale offshore wind and marine current farms composed of variable speed wind turbine driven doubly fed induction generators (DFIGs) and fixed speed squirrel cage induction generators (IGs), respectively. One of the objectives of the proposed scheme is to reduce the overall cost due to the low cost of induction generator. However, induction generator has the stability problem as it requires large amount of reactive power to restore electromagnetic torque during grid disturbance. The proposed cooperative scheme will help marine current generators (IGs) in a marine current farm to provide necessary reactive power demand from their surrounding wind generators (DFIGs) resides in a offshore wind farm without installing additional reactive power compensating devices (STATCOM/SVC). Optimum capacities of wind and marine current farms that can be used in proposed scheme to augment the stability of both farms are also determined, in this study. Different types of fault conditions are examined and the effectiveness of the proposed control scheme is demonstrated by using laboratory standard power system simulator PSCAD/EMTDC.